Application of Photochemistry Principles, Models, and Simulations in Studying Gaseous Components of Space Bodies and Interstellar Matter - Krečo, Anes; Biščević, Helena; Handžić, Azra; Gojak-Salimović, Sabina (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2018)
Space exploration was from its inception multidisciplinary field of research. Whether it is a design of devices that separate light into it different wavelengths, comparison of extracted data to known characteristics of spectrum of molecules, engineering of complex autonomous system of interplanetary probes or intricate calculations of vehicle trajectories, the objective was the same, understanding of the Universe around us. Chemistry as fundamental natural science finds its place in the area known as astrochemistry. When it comes to direct experimentation most of work is done on board the remotely operated space probes that are often self-enclosed laboratories on other space objects or orbiters. However, data collected by these is overshadowed by sheer volume of information extracted from light collected by Earth and space-based observatories and it is here that photochemistry takes the prime role. In last few decades, with development of computing technology, mathematical models have taken root in interpreting data collected by observations and predicting the characteristics of objects analogous to already well-studied ones. Several of the recent studies in this field have been discussed in this paper.